Enhancing Pomegranate Yield Through Biological Control of Shot Hole Borer: A Comparative Studyy - Shivam Satyawan Madrewar; Nimisha Ravindra Khadkikar; Ashish Madhukar Rajnor; Mayuri Sanjay Mane; Atharva Manish Gumphekar; Rutuja Bajarang Thombare (International Journal of Sustainable Applied Sciences, 2024)
This study demonstrates the potential of Beauveria bassiana, Metarhizium anisopliae, and Trichogramma spp. as effective biological control agents against the Shot Hole Borer in pomegranate orchards. The findings suggest that these bioagents can be integrated into existing pest management programs, offering a viable and environmentally sustainable alternative to chemical pesticides. This research contributes to the broader field of sustainable agriculture and highlights the importance of biological control in managing pest populations in fruit crops.